2013
DOI: 10.1002/adma.201305169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PbI2 Single‐Layered Inorganic Nanotubes Encapsulated Within Carbon Nanotubes

Abstract: The template assisted growth of single-layered inorganic nanotubes is reported. Single-crystalline lead iodide single-layered nanotubes have been prepared using the inner cavities of carbon nanotubes as hosting templates. The diameter of the resulting inorganic nanotubes is merely dependent on the diameter of the host. This facile method is highly versatile opening up new horizons in the preparation of single-layered nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 55 publications
6
64
0
Order By: Relevance
“…The long range van der Waals (vdW) interaction between monolayer PbI2 and Graphene is accounted by zero damping DFT-D3 method of Grimme. the distance between top and bottom I-Pb atom layers are 4.66 Հ and 3.72 Հ respectively, which are in good agreement with the experimental bulk values 39 . 1 (a) and (b), respectively).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The long range van der Waals (vdW) interaction between monolayer PbI2 and Graphene is accounted by zero damping DFT-D3 method of Grimme. the distance between top and bottom I-Pb atom layers are 4.66 Հ and 3.72 Հ respectively, which are in good agreement with the experimental bulk values 39 . 1 (a) and (b), respectively).…”
Section: Methodssupporting
confidence: 89%
“…Carbon nanotube encapsulated within single layer PbI 2 nanotube has been fabricated in most recent experiment 39. have shown that the combination of highly conductive graphene and optically active molybdenum disulphide (MoS 2 ) into a new family of 2D van der Waals (vdW) hetero-structure can photo-excite electron-hole pairs within MoS 2 's band-gap, allowing achieving enhanced photocurrent in the visible light region.…”
mentioning
confidence: 99%
“…The etching occurred only at the interface between the iron nanoparticles and the nanotubes. Steam purified carbon nanotubes are being employed for a wide range of applications such as lithium-ion batteries [26], supercapacitors [27,28], ceramic composites [29], templated growth of novel structures [30], biomedical applications [31,32] or even for the formation of graphene by unzipping steam purified nanotubes [28]. Furthermore, initial studies reveal that short SWCNTs can be obtained after prolonged steam treatment [23].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by most recent experiment on a van der Waals nanohybrid between lead iodide (PbI 2 ) and carbon nanotube, we have carried out systematic DFT studies on a 2D graphene/PbI 2 van der Waals heterostructure and revealed a significant red‐shift compared with the pure PbI 2 nanosheet as shown in Figure (a) . The approach was then extended to 2D bismuth iodide (BiI 3 ), an experimentally unexplored 2D material.…”
Section: Modulating Optical Properties In 2d Van Der Waals Heterostrumentioning
confidence: 99%